(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India, being the largest democracy in the world, stands at that juncture of history where its youth, comprising more than 65% of its population, has immense potential to shape its democratic future. This study basically tries to find out the role of Indian youths in strengthening democracy through political, social, and economic processes. But such youth engagement in democratic activities like voting, activism, and civil society movements would ensure that the democratic system becomes more rejuvenated; inclusiveness and transparency would be assured. Yet, political apathy, underrepresentation, and socioeconomic inequalities are holding back this holistic participation of youth. As the study indicates, education, digital literacy, and social media platforms are some of the crucial elements required for giving a fillip to today’s youth for a better, effective, and qualitative engagement in the democratic process. The paper further talks about the reforms required in the political system that would allow more youths in decision-making positions. This paper reflects that young people can be central to democratic governance and sustainable development through the critical examination of initiatives and youth-driven movements in India. This study gives insight, in essence, into how active youth participation can make democracy stronger in its foundations by being more inclusive and active for years to come.